The Jarisch-Herxheimer Reaction on Secondary Syphilis Patient with Roseola Syphilitica and Human Immunodeficiency Virus Co-Infection: A Case Report - Dwi Puspawati, Ni Made; I Gusti Ayu Agung Elis Indira; Adelia Suryani; Putu Setiani (HM Publisher, 2024)
Background: The Jarisch-Herxheimer reaction is an inflammatory reaction that occurs within 12 hours after administration of antibiotic therapy for spirochaeta species like Treponema pallidum. The reaction includes fever, headache, reappearing or worsening of skin lesions, lymphadenopathy, pharyngitis, malaise, and myalgias. Case presentation: We present a 27-year-old man complaining of high fever 4 hours after the injection of benzathine penicillin. The patient also complained of headaches, body aches and aches. There were no complaints of shortness of breath, itching, skin blisters, red eyes, or sores on the genitals. History of take any medication was denial by the patient. After treatment by giving antipyretics and corticosteroids and getting enough rest, in the 24 hours, the patient was improved. Conclusion: The Jarisch-Herxheimer reaction is an inflammatory reaction that occurs after the administration of antibiotic therapy for spirochaeta species like Treponema pallidum.